Coccolithophores in an Acidifying Ocean: from Single Strain to Multiple Species Approaches - Krug, Sebastian A. (2011)
The human induced global climate change has severe consequences for the marine systems. Oceans have absorbed 50% of anthropogenic carbon dioxide emissions, consequently, attenuating global atmospheric warming. However, once entering the oceans, CO2 loses its inert characteristics. By the reaction with water it forms carbonic acid resulting in the phenomenon latterly referred to as ocean acidification. In the last two centuries, with the beginning of the industrial revolution, the global mean surface pH was already reduced by 0.1 units. Within the next 90 years the acidity level is believed to drop by another 0.35 units. Based on a simple causality a given atmospheric partial pressure of CO2 can easily be transferred into surface ocean carbon chemistry. Nevertheless, implications for the marine biota caused by increasing ocean acidification are complex and difficult to assess. Although the effects of rising pCO2 have been shown on single species of corals, pteropods, foraminifera, diverse phytoplankton species and larvae of echinoderms and fishes, research is far from understanding correlations between single species response and ecosystem functioning. Based on the importance as the most prominent pelagic calcifier and their hypothesised functioning as carbon export ballast, coccolithophores are among the best evaluated species with respect to ocean acidification. Calcification and photosynthesis has turned out to be sensitive to future conditions, however, with highly variable responses among species and species strains. For most analysed species calcification declined with rising pCO2, also the production of organic matter usually decreased, but turned out to rise for Gephyrocapsa oceanica. Surprisingly, the species Coccolithus braarudii appeared to be insensitive to an elevation of pCO2 from 380 µatm to 750 µatm. Based on this intriguing picture of coccolithophore response to ocean acidification this dissertation was concerned with the following questions: Does the insensitivity of C. braarudii to ocean ...